On the Cauchy problem for the two‐component b‐family system. (21st March 2013) - Zhu, Min; Xu, Junxiang
<x xml:space="preserve">Abstract</x> In this paper, we establish the local well‐posedness for the two‐component b‐family system in a range of the Besov space. We also derive the blow‐up scenario for strong solutions of the system. In addition, we determine the wave‐breaking mechanism to the two‐component Dullin–Gottwald–Holm system. Copyright © 2013 John Wiley & Sons, Ltd.